Managerial economics applications, strategy, and tactics - McGuigan, James R. (South-Western College, 1999)
With its emphasis on real world, manager-oriented applications, this text shows students how managers apply theories and techniques to analyze and solve real-world business problems. Over 200 applications, corporate examples, and "managerial challenges" support this approach.